Structure and functioning of four North Atlantic ecosystems - A comparative study. (October 2020) - Melle, Webjørn; Klevjer, Thor; Drinkwater, Kenneth F.; Strand, Espen; Naustvoll, Lars Johan; Wiebe, Peter H.; Aksnes, Dag L.; Knutsen, Tor; Sundby, Svein; Slotte, Aril; Dupont, Nicolas; Vea Salvanes, Anne Gro; et al.
Abstract: The epi- and mesopelagic ecosystems of four sub-polar ocean basins, the Labrador, Irminger, Iceland and Norwegian seas, were surveyed during two legs from Bergen, Norway, to Nuuk, Greenland, and back to Bergen. The survey was conducted from 1 May to 14 June, and major results were published in five papers (Drinkwater et al., Naustvoll et al., Strand et al., Melle et al., this issue, and Klevjer et al., this issue a, this issue b). In the present paper, the structures of the ecosystem are reviewed, and aspects of the functioning of the ecosystems examined, focusing on a comparison of trophic relationships in the four basins. In many ways, the ecosystems are similar, which is not surprising since they are located at similar latitudes and share many hydrographic characteristics, like input of both warm and saline Atlantic water, as well as cold and less saline Arctic water. Literature review suggests that total annual primary production is intermediate in the eastern basins and peaks in the Labrador Sea, while the Irminger Sea is the most oligotrophic sea. This was not reflected in the measurements of different trophic levels taken during the cruise. The potential new production was estimated to be higher in the Irminger Sea than in the eastern basins, and while the biomass of mesozooplankton was similar across basins, the biomass of mesopelagic micronekton was about one order of magnitude higher in the western basins, and peaked in the Irminger Sea, where literature suggests annual primary production is at its lowest. The eastern basins hold huge stocks of pelagic planktivore fish stocks like herring, mackerel and blue whiting, none of which are abundant in the western seas. As both epipelagic nekton and mesopelagic micronekton primarily feed on the mesozooplankton, there is likely competitive interactions between the epipelagic and mesopelagic, but we're currently unable to explain the estimated 1 order of magnitude difference in micronekton standing stock. The results obtained during the survey highlight that even if some aspects of pelagic ecosystems are well understood, we currently do not understand overall pelagic energy flow in the North Atlantic.